2015
DOI: 10.1089/jpm.2014.0226
|View full text |Cite
|
Sign up to set email alerts
|

Complex Chronic Conditions in Rhode Island's Pediatric Populace: Implications for Palliative and Hospice Services, 2000–2012

Abstract: CCCs constitute a significant proportion of medically related pediatric deaths in Rhode Island and are associated with both secondary comorbidities and death at home. Specialized, multidisciplinary services are warranted and PP/HC is crucial for patient and family support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…22,23 Despite the burden of MCCs on children, families, communities, and health care systems, the epidemiological assessment of children with MCCs within a geographically defined pediatric US population has not been previously performed. Although valuable, the extant literature is limited to cohorts derived from databases originating from health care use,* payer source, 4,[7][8][9][10]14,20,[30][31][32][33] death certificates, [34][35][36][37] and national surveys. 38,39 Furthermore, the reported prevalence for chronic disease in children is widely variable (0.2%-44%) because of considerable heterogeneity in study definitions, designs, populations, and conditions.…”
mentioning
confidence: 99%
“…22,23 Despite the burden of MCCs on children, families, communities, and health care systems, the epidemiological assessment of children with MCCs within a geographically defined pediatric US population has not been previously performed. Although valuable, the extant literature is limited to cohorts derived from databases originating from health care use,* payer source, 4,[7][8][9][10]14,20,[30][31][32][33] death certificates, [34][35][36][37] and national surveys. 38,39 Furthermore, the reported prevalence for chronic disease in children is widely variable (0.2%-44%) because of considerable heterogeneity in study definitions, designs, populations, and conditions.…”
mentioning
confidence: 99%
“…The study also showed that most deaths occur in emergency units or at home, while a small number in palliative care institutions, which reflects the scarcity of this type of service 17 . However, the insufficient documentation to clarify PPC offer and the types of intervention can be pointed out as a limitation of this cohort study that started from inferences based on death certificates 17 .…”
Section: Importance Of the Interdisciplinary Teammentioning
confidence: 95%
“…Four articles included in the sample were published in 2014 10,18,19,21 , two in 2015 13,17 , five in 2016 15,16,20,22,23 , two in 2017 12,14 and one in 2018 11 . All studies were produced outside Brazil.…”
Section: Data Characterizationmentioning
confidence: 99%
See 2 more Smart Citations